1995
DOI: 10.1073/pnas.92.21.9638
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 95-kDa WEE1-like tyrosine kinase in HeLa cells.

Abstract: Human WEEl (WEEJHu) was cloned on the basis of its ability to rescue weel+ mutants in fission yeast [Igarashi, M., Nagata, A., Science 257, 1955Science 257, -1957. To study the regulation of WEEJHu in human cells, two polyclonal antibodies to bacterially produced p49WEE1Hu were generated. In addition, a peptide antibody generated against amino acids 361-388 of p49WEE1Hu was also used. Unexpectantly, these antibodies recognized a protein with an apparent molecular mass of 95 kDa in HeLa cells, rather than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 22 publications
3
37
0
1
Order By: Relevance
“…In mammalian somatic cells, the fate of wee1 is less clear: some studies found that wee1 protein was reduced during mitosis (Baldin and Ducommun, 1995;Watanabe et al, 1995), whereas others found that it was stable (McGowan and Russell, 1995;Parker et al, 1995). In Xenopus egg extracts, immunoblots of endogenous wee1 show that overall wee1 protein levels are essentially constant across the early embryonic cell cycles (Walter et al, 1997), a point that we confirm here.…”
Section: Regulation Of Wee1 At the Level Of Proteolysis?supporting
confidence: 72%
“…In mammalian somatic cells, the fate of wee1 is less clear: some studies found that wee1 protein was reduced during mitosis (Baldin and Ducommun, 1995;Watanabe et al, 1995), whereas others found that it was stable (McGowan and Russell, 1995;Parker et al, 1995). In Xenopus egg extracts, immunoblots of endogenous wee1 show that overall wee1 protein levels are essentially constant across the early embryonic cell cycles (Walter et al, 1997), a point that we confirm here.…”
Section: Regulation Of Wee1 At the Level Of Proteolysis?supporting
confidence: 72%
“…8 The inhibitory phosphorylations of threonine 14 (T14) and tyrosine 15 (Y15) at the ATP-binding pocket are mediated by Wee1 and Myt1 kinases. [9][10][11][12][13] Wee1 is the major kinase phosphorylating the Y15 site. While Myt1 preferentially phosphorylates the T14 site, it can also phosphorylate the Y15 site.…”
Section: © 2 0 0 4 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…The loss of these controlling subunits would certainly account for both the reduction in CDK activity and the lack of any CDK1 Y 15 inhibitory phosphorylation, since Wee1/Myt1 can only phosphorylate this inhibitory site once the cyclin B/CDK1 complex is assembled (Parker et al, 1995;Booher et al, 1997). There are several reported precedents for this.…”
Section: Dmekk3:er* Promotes Down-regulation Of Cyclin a And Cyclin Bmentioning
confidence: 99%